Comparative Study of Ropivacaine Alone Versus Combination of Ropivacaine with Either Dexmedetomidine or Dexamethasone for Ultrasound Guided Supraclavicular Brachial Plexus Block - Pyakurel, Kumud; Khanal, Kanak; Dahal, Sonia (Journal of Karnali Academy of Health Sciences, 2023)
Background: Ropivacaine is common choice for supraclavicular brachial plexus block. Dexmedetomidine and Dexamethasone are frequently added to local anesthetics for improved effects. With limited comparative evidence, study aimed to assess Dexmedetomidine and Dexamethasone as adjuvants to Ropivacaine in ultrasoundguided supraclavicular brachial plexus block.Materials and Methods: This prospective double-blind study enrolled patients aged 18-60, scheduled for elective upper limb surgery below mid-humeral level. They were randomly assigned into three groups: Ropivacaine alone, Ropivacaine with Dexmedetomidine (1 mcg/kg), or Ropivacaine with Dexamethasone (8 mg). Study aimed to compare sensory and motor blockade onset and duration, postoperative analgesia duration, and adverse event occurrence among groups.Results: Ninety-eight patients participated in the study. All three groups showed similar characteristics in terms of age, weight, gender, ASA grade, and surgery duration. Onset and duration of sensory and motor block were comparable between the Dexamethasone and Dexmedetomidine groups. Significant difference was observed when comparing the Ropivacaine only group to either of the other two groups or when comparing all three groups. Similarly, postoperative analgesia duration was comparable between the Dexamethasone and Dexmedetomidine groups while it differed significantly when comparing all three groups or when comparing the Ropivacaine only group to either of the other groups. Ropivacaine with Dexmedetomidine group experienced notable occurrence of bradycardia.Conclusion: Dexamethasone and Dexmedetomidine as adjuvants to 0.5% Ropivacaine for ultrasound-guided supraclavicular brachial plexus blockade have comparable effects on sensory and motor blockade onset and duration, along with postoperative analgesia duration. Dexmedetomidine, however, is linked to more bradycardia compared to Dexamethasone